409 Eleven Years of the Western Maryland Pasture-Based Meat Goat Performance Test. (7th December 2018) - Schoenian, S; O'Brien, D; Semler, J; Gordon, D; Bennett, M
Abstract: The US meat goat industry lags behind other livestock industries in the use of quantitative genetic evaluation. The Western Maryland Pasture-Based Meat Goat Performance Test was initiated in 2006 at the University of Maryland's Western Maryland Research & Education Center (39º 30' N/77º 44' W). The purpose of the test was to identify genetically-superior meat goat bucks, especially those which exhibited resistance and resilience to internal parasites. From 2006–2016, 736 bucklings, of various breeds and crosses, were evaluated. One hundred producers from 20 states consigned one or bucks. Bi-weekly progress reports, summaries, and other information and data were shared via a blog (https://mdgoattest.blogspot.com ), which has 218, 346 cumulative page views from 523 blog posts. Many other programs were held in conjunction with the test, including sales, field days, youth programs, and carcass evaluation. Each year, top-performing bucks were identified and sold or retained for breeding, with 86% of consigners using the genetics from top-performing bucks in their breeding programs. Many more producers used the genetics from top-performing bucks by purchasing breeding stock and/or semen from consigners. Per survey data, consigning to the Maryland test improved the reputation of participating herds (80%), increased the demand and selling price for breeding stock (66–72%), and enabled the sale of semen from top-performers (38%). The test enabled participating producers to develop more parasite resistant herds (76%), improve the health and performance of their herds (73%), and improve their knowledge of parasite control (80%). The Western Maryland Pasture-Based Meat Goat Performance Test provided economic value to producers (71%), while contributing to the genetic improvement of the meat goat industry and serving as a valuable resource to producers.